Optical properties of AlxGa1-xP (0 <= x <= 0.52) alloys - Choi, SG; Kim, YD; Yoo, SD; Aspnes, DE; Woo, DH; Kim, SH (AMER INST PHYSICS, 2000)
We report optical properties of AlxGa1-xP (0 less than or equal to x less than or equal to 0.52) alloys grown by gas source molecular-beam epitaxy on S-doped GaP(001) substrates. Room-temperature pseudodielectric function spectra from 1.5 to 6.0 eV were obtained by spectroscopic ellipsometry. By applying the parabolic-band critical point model to numerically calculated second energy derivatives of these spectra, we obtained accurate room-temperature values of the E-1, E-0', E-2, and E-2' critical point energies and their dependence on composition x. (C) 2000 American Institute of Physics. [S0021-8979(00)01003-3].
Keywords: MOLECULAR-BEAM EPITAXY; DIELECTRIC FUNCTION; TEMPERATURE-DEPENDENCE; INTERBAND-TRANSITIONS; ALGAP ALLOYS; GAP; GROWTH; SILICON; GAAS